(untitled) (Medico Legal Update, 2021)
The quality of higher education has become one of the main challenges facing educational systems in the last two decades. The promotion of services in the field of education and scientific research require active management that continuously improves academic services. In this study, after identifying the indicators of the quality of higher education services, a questionnaire was distributed to 15 experts in order to elite the quality of higher education services in the university to assess these indicators and select the best effective ones. Then, a second questionnaire was provided to eight experts to evaluate the performance and the weight of these criteria in the university by using Gray weights. The result of research revealed that the staff has the highest score and the university has a solid foundation. In order to reduce the existing gap, relevant academic subjects related to the disciplines need to be provided. Access to administrative services was improved, as well as electronic office services tailored to students’ needs. In order to reduce the gap created for the environmental index, wider green space need to be developed within the university and increasing the opportunity for free web access and free access to valid and up-todate scientific resources are needed.